Effects of Hydrogen Passivation on Fullerene-Derived Si30C30 Clusters - Alathlawi, Hussain J.; Alkhaldi, Noura D.; Huda, Muhammad N. (Frontiers in Materials, 2020)
Silicon carbide (SiC) is technologically a significant material. A recent report on the abundance of C60 fullerenes in interstellar space, along with the presence of the SiC precursors, sparked interest in potentially similar SiC nanostructures. The C60 fullerene was found experimentally and is an exceptionally stable form of carbon. As Si and C have similar valence electron properties, it has been long envisioned that Si and SiC could also form similar fullerene type structures. In this paper, Si30C30 fullerene-derived clusters were studied from the first principle starting from an ideal Si60 fullerene templet with various arrangements of silicon and carbon atoms, and then relax them without any symmetry constraint. Hydrogen passivation was considered as well to model the effect of ligands that may be available during the chemical synthesis processes. We have found that after passivation, the relative stability of different configurations of Si30C30 clusters changed compared to the unpassivated structures, while some structures collapsed. We have also noticed several Si-Si and Si-C double bonds in the unpassivated structures. Upon relaxation, some Si atoms lost their hydrogen, while carbon atoms capture those hydrogen atoms. Finally, we tested the endohedral doping of a transition metal, tungsten atom, to stabilize and magnetize Si30C30. With hydrogen passivation, the magnetic moment on W atom was enhanced. Overall, the effects of passivation on these fullerene structures are not very straightforward.